WHO resource book on mental health, human rights and legislation (WHO, 2005)
The WHO Resource Book on Mental Health, Human Rights and Legislation brings together important information on international human rights standards related to mental health. It provides practical guidance on key issues that countries need to consider and incorporate into their national mental health laws, as well as useful strategies to facilitate the development, adoption and implementation of the laws. The Resource Book is illustrated throughout with examples of diverse experiences and practices, as well as extracts of laws and other law-related documents from different countries. It also contains a Checklist on mental health legislation which countries can use to review the comprehensiveness and adequacy of existing mental health legislation and to help them in the process of drafting a new law.
Keywords: lidská práva; rozvojové země; směrnice jako téma; právo, zákonodárství; duševní zdraví; hygiena; Human Rights; zdravotní politika; Health Policy; psychiatrie; zákonodárství jako téma; Guidelines as Topic; Mental Health; Legislation as Topic; Developing Countries